Editorial - Jonker, Louis C. (Stellenbosch theological journal, 2024)
In January 2023, representatives of the Global Network for Theology and Religion (GN) convened at the Faculty of Theology, Stellenbosch University. It was the third international conference of the network. In 2009, a founding meeting was held in Heidelberg, Germany, where a Memorandum of Understanding (http://globalnetresearch.org/cms/wp-content/uploads/2017/05/memorandum_of_understanding-1.pdf) was accepted by the institutions present. The main impetus behind the founding of the GN was prof dr. Michael Welker of Heidelberg University who—through the Research Center for International and Interdisciplinary Theology, University of Heidelberg (FIIT)—started forming personal networks from 2007.